Glioblastoma multiforme: Effect of hypoxia and hypoxia inducible factors on therapeutic approaches - Wenjuan Huang; Weiwei Chen; Xia Zhang (2016)
Central nervous system-based cancers have a much higher mortality rate with the 2016 estimates at 6.4 for incidence and 4.3 for deaths per 100,000 individuals. Grade IV astrocytomas, known as glioblastomas are highly aggressive and show a high proliferation index, diffused infiltration, angiogenesis, microvascular proliferation and pleomorphic vessels, resistance to apoptosis, and pseudopalisading necrosis. Extensive hypoxic regions in glioblastomas contribute to the highly malignant phenotype of these tumors. Hypoxic regions of glioblastoma exacerbate the prognosis and clinical outcomes of the patients as hypoxic tumor cells are resistant to chemo- and radiation therapy and are also protected by the malfunctional vasculature that developed due to hypoxia. Predominantly, hypoxia-inducible factor-1α, vascular endothelial growth factor (VEGF)/VEGF receptor, transforming growth factor-β, epidermal growth factor receptor and PI3 kinase/Akt signaling systems are involved in tumor progression and growth. Glioblastomas are predominantly glycolytic and hypoxia-induced factors are useful in the metabolic reprogramming of these tumors. Abnormal vessel formation is crucial in generating pseudopalisading necrosis regions that protect cancer stem cells residing in that region from therapeutic agents and this facilitates the cancer stem cell niche to expand and contribute to cell proliferation and tumor growth. Therapeutic approaches that target hypoxia-induced factors, such as use of the monoclonal antibody against VEGF, bevacizumab, have been useful only in stabilizing the disease but failed to increase overall survival. Hypoxia-activated TH-302, a nitroimidazole prodrug of cytotoxin bromo-isophosphoramide mustard, appears to be more attractive due to its better beneficial effects in glioblastoma patients. A better understanding of the hypoxia-mediated protection of glioblastoma cells is required for developing more effective therapeutics.